2007
DOI: 10.1021/cm702251f
|View full text |Cite
|
Sign up to set email alerts
|

Titania−Sepiolite Nanocomposites Prepared by a Surfactant Templating Colloidal Route

Abstract: Microfibrous TiO2−sepiolite and TiO2/SiO2−sepiolite nanocomposites were prepared following a colloidal route based on the controlled hydrolysis of alkoxides in the presence of cetyltrimethylammonium−sepiolite gel. In this way, titanium(IV) isopropoxide and tetramethoxysilane were used as titania and silica precursors, respectively, being incorporated within the organophilic layer developed on the surface of the silicate microfibers and further hydrolyzed in this region. The hydrolysis of the precursor gives hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 51 publications
6
90
2
5
Order By: Relevance
“…It has also been used in conjunction with PVA to form hydrogel fibres where the degree of swelling can be easily controlled by the degree of crosslinking [30]. [30][31][32]. It is composed of blocks, which are characterized by a sandwich structure of a central magnesium octahedral sheet between two silica tetrahedral sheets, forming a capillary network of parallel channels [31][32][33].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used in conjunction with PVA to form hydrogel fibres where the degree of swelling can be easily controlled by the degree of crosslinking [30]. [30][31][32]. It is composed of blocks, which are characterized by a sandwich structure of a central magnesium octahedral sheet between two silica tetrahedral sheets, forming a capillary network of parallel channels [31][32][33].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is composed of blocks, which are characterized by a sandwich structure of a central magnesium octahedral sheet between two silica tetrahedral sheets, forming a capillary network of parallel channels [31][32][33]. Sepiolite features a large specific surface area in the region of 140 -320m 2 /g [31,34], and its interactions with polymer(s) not only take place on the external surface, due to the significant number of silanol (Si-OH) groups but by penetration into the structural channels of sepiolite fibre blocks [35,36]. Previous studies demonstrated good reinforcing capability of sepiolite in polymeric matrices and such reinforcements were obtained at low sepiolite contents, typically lower than 10wt.% [37,38].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…To avoid the complications, a silane coupling agent is needed to improve silica-rubber interaction and silica dispersion as well as to prevent accelerator adsorption on the silica surface [5][6][7][8][9]. Sepiolite is a hydrated magnesium silicate clay (Mg2H2SiO3O9.xH2O), Sepiolite has a similar structure to the layered structure of montmorillonite except that the layers lack continuous octahedral sheet [10][11]. The acicular morphology of sepiolite generally improves adhesion/compatibility with polymeric matrices and provides an excellent reinforcing effect on polymer [12] and sepiolite improved the endothermic nature of decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] This behaviour suggests the involvement of these surface groups in the interaction with the magnetite NPs, in a similar way to that observed in anatase NPs anchored on sepiolite surface. [ 12 ] XRD patterns indicate the preservation of magnetite and sepiolite structures ( Figure S2). The widths of the refl ections are compatible with a magnetite NP average size that is in the order of magnitude of 10 nm, in accordance to TEM observations (Figure 1 b).…”
Section: Doi: 101002/adma201101364mentioning
confidence: 99%